2018
DOI: 10.1007/978-3-319-75402-4_38
|View full text |Cite
|
Sign up to set email alerts
|

Underdeveloped RPE Apical Domain Underlies Lesion Formation in Canine Bestrophinopathies

Abstract: Canine bestrophinopathy (cBest) is an important translational model for BEST1-associated maculopathies in man that recapitulates the broad spectrum of clinical and molecular disease aspects observed in patients. Both human and canine bestrophinopathies are characterized by focal to multifocal separations of the retina from the RPE. The lesions can be macular or extramacular, and the specific pathomechanism leading to formation of these lesions remains unclear. We used the naturally occurring canine BEST1 model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Loss of RPE apical microvilli leading to microdetachment of the retina is thought to be the earliest features of CMR, indicating an RPE-photoreceptor disease interface for bestrophinopathy. 91 , 92 …”
Section: Clinical Spectrum Of Bestrophinopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of RPE apical microvilli leading to microdetachment of the retina is thought to be the earliest features of CMR, indicating an RPE-photoreceptor disease interface for bestrophinopathy. 91 , 92 …”
Section: Clinical Spectrum Of Bestrophinopathiesmentioning
confidence: 99%
“…Loss of RPE apical microvilli leading to microdetachment of the retina is thought to be the earliest features of CMR, indicating an RPE-photoreceptor disease interface for bestrophinopathy. 91,92 Much of the early work examining BEST1 in human cells involved overexpression of the protein in the kidney epithelial cell lines, HEK-293 or MDCKII. 67,93 Yet, RPE cells have a unique polarisation signature, independent of E-Cadherin, where sorting of proteins to the apical and basement membrane for example, Na + /K + ATPase and monocarboxylate transporter 1, is reversed compared to other epithelial cells.…”
Section: Model Systems For Bestrophinopathiesmentioning
confidence: 99%
“…The loss of the RPE apical processes results in a loss of all direct contact of the cones to the RPE, severely impacting the physiological role the RPE has on retinal maintenance. It is hypothesized that the lack of RPE apical processes and subsequent weakened interphotoreceptor matrix is instrumental in the characteristic detachments and lesions observed in diseases caused by BEST1 mutations [93,94]. Interestingly, microdetachments were identified in response to light exposure in pre-clinical CMR dogs.…”
Section: Best1mentioning
confidence: 99%
“…This can also result from a reduced activity of the volume‐activated Cl channel function because the phagocytosis process requires an efficient volume regulation . Furthermore, also the recently reported changes in the RPE apical surface in canine bestrophinopathy support a phagocytosis defect as a loss of RPE function leading to retinal degeneration …”
Section: Introductionmentioning
confidence: 99%
“…22 Furthermore, also the recently reported changes in the RPE apical surface in canine bestrophinopathy support a phagocytosis defect as a loss of RPE function leading to retinal degeneration. 8,23 In addition to the loss of Cl channel activity, a disturbed interaction of mutant bestrophin-1 and its interaction partners contributes to the chain of events leading to macular dystrophy. Due to the considerable number of possible interaction partners for bestrophin-1, Johnson et al 5 concluded that bestrophin-1 is a multifunctional protein.…”
Section: Introductionmentioning
confidence: 99%